Membangun Kampung Kelor : Strategi Peningkatan Ketahanan, Keberlanjutan dan Kearifan Komunitas Rural Sungai Nibung Terhadap Perubahan Iklim - Susanti, Rina; Kadarisman, Yoskar; Asriwandari, Hesti; Hidir, Achmad; Widodo, Teguh (Universitas Muhammadiyah Mataram, 2025)
Abstract: This community service program aims to empower the community through the development of moringa villages as a strategy for increasing resilience, sustainability and wisdom of rural communities towards climate change in Mekar Jaya Hamlet, Sungai Nibung Village. The stages of community service are carried out using the PRA method, including establishing partners, socialization, training in moringa leaf nurseries and processing, and the development of moringa villages. Results of PKM activities in the Mekar Jaya Hamlet community, it was shown that the level of knowledge of participants regarding climate change and the benefits of moringa plants varies greatly. Based on pre-test data, it was shown that 23.53% of participants had a low level of knowledge, while only 5.88% of participants had a high level of knowledge. However, after the provision of socialization materials, there was a significant increase. Based on post-test data, participants with a high level of knowledge jumped to 82.35% and there was no low level of knowledge. This increase shows that the effectiveness of the socialization program in increasing public awareness and understanding of environmental issues and the potential benefits of moringa plants.Abstrak: Program pengabdian ini bertujuan untuk memberdayakan masyarakat melalui pembangunan kampung kelor sebagai strategi peningkatan, ketahanan, keberlanjutan dan kearifan komunitas rural terhadap perubahan iklim di Dusun Mekar Jaya, Desa Sungai Nibung memiliki. Tahapan pengabdian dilakukan dengan metode PRA yang diantaranya, menjalin mitra, sosialisasi, pelatihan pembibitan dan pengolahan daun kelor serta pembangunan kampung kelor. Hasil kegiatan Pengabdian Kepada Masyarakat menunjukkan bahwa tingkat pengetahuan peserta terkait perubahan iklim dan manfaat tanaman kelor sangat beragam. Berdasarkan data pre-test menunjukkan bahwa 23,53% peserta memiliki tingkat pengetahuan yang tergolong rendah, sementara hanya 5,88% peserta memiliki tingkat pengetahuan tinggi. Namun, setelah pemberian materi sosialisasi terjadi peningkatan yang signifikan. Berdasarkan data post-test peserta dengan tingkat pengetahuan tinggi melonjak menjadi 82,35% dan tidak terdapat tingkat pengetahuan rendah. Peningkatan ini adalah menunjukkan bahwa efektivitas program sosialisasi dalam meningkatkan kesadaran dan pemahaman masyarakat terhadap isu lingkungan dan potensi manfaat tanaman kelor.